Avaliação crítica da disciplina Prática Oceanográfica (CG-05028) sob o ponto de vista dos estudantes de graduação do Curso de Oceanografia da Universidade Federal do Pará - DEMARCHI, Cao Güttler (2018)
The Oceanographer is a professional presents a profile where the field activities are very necessary. During its period of training in the course of graduation, disciplines practices, are mandatory for its maturing and reach be awaited with enthusiasm by students, when may pursue-them. This study is a critical evaluation performed with students of the courses of 2000 to 2004 of undergraduate Oceanography of UFPA, which until now had cursado the discipline practice Oceanographic (CG-05028). With the objective of detecting shortcomings in the teaching process learning, as well as inquiry the level of satisfaction and the positive and negative aspects in this process. To this end, questionnaires were applied with questions concerning the issues involved with the discipline. The data obtained were placed in a spreadsheet eletrônicas, where they were generated graphs and presented the results. These showed that the areas of Oceanography (geological, biological and chemical), obtained indexes positive assessments. The area of physical Oceanography has not been analyzed. Despite the positive, makes-if necessary a reassessment, since, new students and teachers joined in the course of graduation in oceanography, taking as aim the improvement of the relationship of learning thee